Investigación participativa y la transformación de las universidades públicas: dar lugar a la producción de conocimiento en modo 2 en organizaciones de modelo II - Greenwood, Davydd J. (Política y Sociedad, 2007)
This article argues that the Western public university is now in full crisis under a determined neo-liberal attack that attempts to undermine the public university as a «public good,» turn it into a vocational training institution, and to reserve high quality higher education to the private sector and to the elites. I argue that action research provides perspectives and strategies for transforming this situation by converting Mode 1 Model I university systems (Tayloristic, hyper-professionalized) into Mode 2 Model II learning organizations intimately connected to their external contexts.